Development of the Koribantes Young Generation Dance for Millennials and Z Generation - Adi Saputra, Surya; Winarno, ME; Hari Wiguno, Lokananta (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2022)
The purpose of the study. The goal to be achieved is to produce a new gymnastics, with the name